The value paradox and its relationship to the psychological health of the lawyer - BENAMER, Wasila; TAHRI, Hamam (Social Sciences Journal)
This study dealt with the issue of value paradox and its relationship to mental health, among a very important segment of society, which is the segment of lawyers. To reveal the ambiguity posed by the questions of the study, two measures were used to collect data, the first is related to the value paradox, and through this it aimed to arrange values in their perceived format, and the second is related to the level of mental health of lawyers, and to know the values and behavior patterns it is necessary to understand the broad base on which societies are based. In its development and building its future, it also aimed to identify the extent of the existence of a correlation between the value paradox and mental health. En savoir plus sur ce texte sourceVous devez indiquer le texte source pour obtenir des informations supplémentaires Envoyer des commentaires Panneaux latéraux